2017
DOI: 10.1007/s40263-017-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Stimulant and Non-Stimulant Medication for Children and Adolescents with ADHD: A Systematic Review and Meta-Analysis of Trials of Methylphenidate, Amphetamines and Atomoxetine

Abstract: BackgroundMany children and adolescents with attention deficit/hyperactivity disorder (ADHD) are treated with stimulant and non-stimulant medication. ADHD medication may be associated with cardiovascular effects. It is important to identify whether mean group effects translate into clinically relevant increases for some individual patients, and/or increase the risk for serious cardiovascular adverse events such as stroke or sudden death.ObjectivesTo evaluate potential cardiovascular effects of these treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(123 citation statements)
references
References 50 publications
(94 reference statements)
4
111
2
6
Order By: Relevance
“…This meta-analysis has confirmed that there were significant increases in post- vs. pre-treatment HR and SBP in children/adolescents and adults receiving methylphenidate or atomoxetine as compared to placebo, which is consistent with recent meta-analysis that reported similar findings in children and adolescents [17]. We further clarified these risks in children/adolescents and adults taking atomoxetine and found atomoxetine caused significant and larger increases in post- vs. pre-treatment HR and SBP as compared to methylphenidate.…”
Section: Discussionsupporting
confidence: 91%
“…This meta-analysis has confirmed that there were significant increases in post- vs. pre-treatment HR and SBP in children/adolescents and adults receiving methylphenidate or atomoxetine as compared to placebo, which is consistent with recent meta-analysis that reported similar findings in children and adolescents [17]. We further clarified these risks in children/adolescents and adults taking atomoxetine and found atomoxetine caused significant and larger increases in post- vs. pre-treatment HR and SBP as compared to methylphenidate.…”
Section: Discussionsupporting
confidence: 91%
“…Those on micronutrients nominally grew more during the 10‐week trial than those on placebo, although the group difference was not significant ( p = .06, ES = 0.40). These results are relevant in view of the adverse effects that stimulants can have on height and blood pressure, both in the short term and long term (Hennissen et al., ; Swanson et al., ; Thapar & Cooper, ). Further, there were few reports among participants of loss of appetite, increased irritability and nausea, side effects frequently associated with stimulant medication (Thapar & Cooper, ).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, our study provides important evidence of the safety and efficacy of LDX in Japanese pediatric patients with ADHD. Additional studies, or pharmacovigilance assessments, would be appropriate in this population to confirm that LDX lacks major potential to cause growth retardation or adverse cardiovascular effects (eg, QTcF prolongation), or to be linked with abuse liability. Further studies specifically in Japanese patients with ADHD would also be useful to clearly define the overall place in therapy of LDX.…”
Section: Discussionmentioning
confidence: 99%